Computing in Civil Engineering 2019 : Visualization, Information Modeling, and Simulation. - Cho, Yong K. (American Society of Civil Engineers, 2019)
This collection contains 80 peer-reviewed papers on visualization, information modeling, and simulation presented at the ASCE International Conference on Computing in Civil Engineering 2019, held in Atlanta, Georgia, June 17-19, 2019.
Keywords: Computer-aided engineering -- Congresses.; Structural analysis (Engineering) -- Data processing -- Congresses.; elektronické knihy; electronic books